SEX RELATED ANNUAL VARIATIONS IN THE CHOLESTEROL CONTENTS OF SOME TISSUES OF A TELEOST, WALLAGO ATTU - JOSHI, B. D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
Cholesterol contents of liver, ovary, testes and muscles of Wallago attu show conspicuous cyclic fluctuations. The changes are more prominent in the female fish, than in the male. Higher values of cholesterol were usually found during the pre-spawning and the spawning period. - Lower values were either in spawning period or immediately after spawning. The liver and muscle cholesterol contents are rapidly replenished, during spent phase of the fish.